Antihyperglycaemic Activity of Standardised Ethanolic Extract of Swietenia macrophylla King Seeds on Goto-Kakizaki Type 2 Diabetic Rats - Meyyammai Swaminathan; Mariam Ahmad; Khairul Niza Abdul Razak; Nor Adlin Yusoff; Gabriel Akyirem Akowuah; Elaine Hui-Chien Lee; Syed Azhar Syed Sulaiman; Mun Fei Yam; Faradianna E. Lokman; Sue Hay Chan; Bey Hing Goh; Vikneswaran Murugaiyah (Tropical Life Sciences Research, 2025)
Swietenia macrophylla (S. macrophylla), commonly known as “sky fruit”, belongs to the Meliaceae family and is predominantly distributed in the neotropical areas of Central America, Southern Asia and the Pacific region. The plant has a rich tradition of being utilised for its anti-diabetic properties and other health benefits. This study focused on the S. macrophylla seeds ethanolic extract (SMEE) to explore its antihyperglycemic effects in Goto-Kakizaki (GK) Type 2 diabetic rats. Bioactive compounds were extracted using maceration, and a reversed-phase high-performance liquid chromatography (RPHPLC) method was validated to separate two limonoids, swietenine and 3,6-O,O diacetyl swietenolide, from the extracts. The 500 mg/kg SMEE dosage significantly reduced fasting blood glucose levels, making it the selected treatment dose. The SMEE group consistentlyimproved glucose regulation during oral glucose tolerance test (OGTT) on the first (9.88 ± 0.69 mmol/L) and eighth (6.12 ± 0.30 mmol/L) days, showing lower initial fasting blood glucose levels. The RP-HPLC method validation confirmed high linearity, ensuring precise quantification within the 1.56 ?g/mL to 200 ?g/mL range for swietenine and 3,6-O,O diacetyl swietenolide. The content of these compounds in 1 mg of SMEE was determined as 27.5 ?g (2.75%) and 14.53 ?g (1.45%), respectively. This study provides robust evidence supporting the antihyperglycaemic properties of S. macrophylla seeds. Future studies could evaluate the long-term metabolic effects of S. macrophylla extract on glucose metabolism, oxidative stress and liver function.